Transcranial direct current stimulation for the treatment of major depressive disorder: A meta-analysis of randomized controlled trials - Wang, Yuan (Psychiatry research, 2019)
lMajor depressive disorder (MDD) is a common and refractory mental disorder.lTranscranial direct current stimulation is a promising method to treat MDD.lFuture trials should be designed to cover long follow-up periods. Major depressive disorder (MDD) is a common and refractory mental disorder. Although antidepressant drugs may be effective for treating MDD, a number of patients do not improve with pharmacologic treatment. Novel therapeutic strategies which are safer and more effective are of great significance in the treatment of MDD. Transcranial direct cranial stimulation (tDCS) is a promising intervention for treating MDD, and it has demonstrated antidepressant effects and beneficial effects on cognitive function. The aim was to assess the efficacy of tDCS as a treatment for MDD. Four databases including PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), China National Knowledge Infrastructure (CNKI) and Wanfang database were searched for articles related to tDCS and major depression. The mean difference (MD) and 95% confidence interval (CI) were calculated in this study. A significant difference between tDCS compared with the control group in Montgomery-Asberg depression rating scale (MADRS) was found. There was a significant statistical difference between tDCS and the control group in Hamilton Depression Rating Scale, 17-items (HDRS-17). This study demonstrated that the intervention of active tDCS was superior to the use of sham tDCS in improving MDD. Furthermore, tDCS might be an effective treatment for MDD.